Articular cartilage calcification of the hip and knee is highly prevalent, independent of age but associated with histological osteoarthritis: evidence for a systemic disorder. Issue 12 (December 2016) - Hawellek, T.; Hubert, J.; Hischke, S.; Krause, M.; Bertrand, J.; Pap, T.; Püschel, K.; Rüther, W.; Niemeier, A.
Summary: Objectives: Based on the concept of a systemic predisposition for articular cartilage calcification (CC), the aim of this study was to determine the prevalence and amount of bilateral CC of hip and knee joints in an unselected sample cohort by high-resolution digital contact radiography (DCR) and to analyze the association of CC with histological OA. Methods: Both hip and knee joints of 87 donors (48 m and 39 f; mean age 62) were analyzed by DCR in this post-mortem study of an unselected cohort of donors. Histological OA (OARSI) of the main load bearing area of femoral heads and medial femoral condyles was determined. Results: The prevalence of CC of the femoral head was 96.6%, of the knee 94.3%. Bilateral calcification was detected in 79.3% of hips and 86.2% of knees. Concomitant CC of all four joints was detected in 69.0% of donors. There was no difference between the amount of CC of hips and knees ( P = 0.47). The amount of CC of any given hip or knee correlated with that of the contralateral hip ( r s = 0.54, P < 0.001) or knee ( r s = 0.50, P < 0.001). There was a correlation between the amount of CC and histological OA (hips r s = 0.48, P < 0.001, knees r s = 0.30, P = 0.004), but not between CC and age (hips r s = −0.09, P = 0.42; knees r s = 0.10, P = 0.34). Conclusions: These data support the concept that articular CC occurs as the result of a systemic disorder. CC appears to be an early element of hip and knee OA pathogenesis independent of age.